A Novel Approach for Combating Klebsiella pneumoniae Biofilm Using Histidine Functionalized Silver Nanoparticles - Chhibber, Sanjay; Gondil, Vijay S.; Sharma, Samrita; Kumar, Munish; Wangoo, Nishima; Sharma, Rohit K. (Frontiers in Microbiology, 2017)
Treating pathogens is becoming challenging because of multidrug resistance and availability of limited alternative therapies which has further confounded this problem. The situation becomes more alarming when multidrug resistant pathogens form a 3D structure known as biofilm. Biofilms are formed in most of the infections especially in chronic infections where it is difficult to eradicate them by conventional antibiotic therapy. Chemically synthesized nanoparticles are known to have antibiofilm activity but in the present study, an attempt was made to use amino acid functionalized silver nanoparticles alone and in combination with gentamicin to eradicate K. pneumoniae biofilm. Amino acid functionalized silver nanoparticles were not only able to disrupt biofilm in-vitro but also led to the lowering of gentamicin dose when used in combination. To the best of our knowledge, this is the first study demonstrating the application of amino acid functionalized silver nanoparticles in the eradication of young and old K. pneumoniae biofilm.